PENERAPAN TEKNOLOGI INFORMASI DALAM PENGELOLAAN ADMINISTRASI DAYAH: STUDI KASUS DI DAYAH BABUSSALAM AL-HANAFIYAH - Marjuita Yanti (STKIP Pesisir Selatan, 2026)
Dayah, as a traditional Islamic educational institution in Aceh, faces challenges in manual administration, including documentation, reporting, data management of students and teachers, as well as academic and financial information systems. This study aims to analyze the application of information technology in the digitization of dayah administration and identify its impact on the effectiveness and efficiency of administrative management at Dayah Babussalam Al-Hanafiyah. Through a qualitative approach using case study methods, this study shows that the application of information technology includes a database management system for students and teachers, integrated academic and financial information applications, and a digital documentation and reporting system. The implementation faced obstacles in the form of limited human resources, infrastructure, and resistance to change, but it succeeded in improving administrative efficiency by reducing processing time from 2-3 weeks to 2-3 days, increasing data accuracy through automatic validation, and improving management transparency. The digitization of administration through the application of information technology has proven to be effective in improving the quality of dayah management, with the caveat that ongoing training, adequate infrastructure support, and the commitment of all stakeholders to the sustainability of the system are necessary.